2022
DOI: 10.1186/s12575-022-00180-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Factors and Integrated Multi-Omics Studies Identify Potential Novel Therapeutic Targets for Pediatric Desmoid Tumor

Abstract: Background Desmoid tumor (DT), also known as desmoid-type fibromatosis (DTF) or aggressive fibromatosis (AF) is a rare mesenchymal tumor affecting both children and adults. It is non-metastasis but infiltrative, growing with a high recurrence rate to even cause serious health problems. This study investigates the biology of desmoid tumors through integrated multi-omics studies. Methods We systematically investigated the clinical data of 98 extra-ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Similar alterations have been shown to increase tumorigenesis in other tumor types but have not been canonically demonstrated in desmoid fibromatosis. 32 The low clinical pattern of recurrence in our series of SNM (12.5%; 1/8 cases), as compared with the high rate of recurrence ( > 65%) seen in desmoid fibromatosis, particularly after resection 33 additionally highlights a striking biologic difference. In a series by Flucke et al, 20 3 pediatric patients were identified with exon 3 CTNNB1 alterations in head and neck desmoid tumors.…”
Section: Discussionmentioning
confidence: 70%
“…Similar alterations have been shown to increase tumorigenesis in other tumor types but have not been canonically demonstrated in desmoid fibromatosis. 32 The low clinical pattern of recurrence in our series of SNM (12.5%; 1/8 cases), as compared with the high rate of recurrence ( > 65%) seen in desmoid fibromatosis, particularly after resection 33 additionally highlights a striking biologic difference. In a series by Flucke et al, 20 3 pediatric patients were identified with exon 3 CTNNB1 alterations in head and neck desmoid tumors.…”
Section: Discussionmentioning
confidence: 70%